Same admission laparoscopic cholecystectomy for acute cholecystitis: is the "golden 72 hours" rule still relevant?. Issue 1 (January 2017) - Tan, Jarrod K.H.; Goh, Joel C.I.; Lim, Janice W.L.; Shridhar, Iyer G.; Madhavan, Krishnakumar; Kow, Alfred W.C.
Abstract: Background: Studies have shown that same admission laparoscopic cholecystectomy (SALC) is superior to delayed laparoscopic cholecystectomy for acute cholecystitis (AC). While some proposed a"golden 72-hour" for SALC, the optimal timing remains controversial. The aim of the study was to compare the outcomes of SALC in AC patients with different time intervals from symptom onset. Methods: A retrospective analysis of 311 patients who underwent SALC for AC from June 2010–June 2015 was performed. Patients were divided into three groups based on the time interval between symptom onset and surgery: <4 days (E-SALC), 4–7 days (M-SALC), >7 (L-SALC). Results: The mean duration of symptoms was 2(1–3), 5(4–7) and 9 (8–13) days for E-SALC, M-SALC and L-SALC, respectively ( p  < 0.001). Conversion rates were higher in the L-SALC group [E-SALC, 8.2% vs M-SALC, 9.6% vs L-SALC, 21.4%] ( p  = 0.048). The total length of stay was longer in patients with longer symptom duration [E-SALC, 4 (2–33) vs M-SALC, 2 (2–23) vs L-SALC, 7 (2–49)] ( p  < 0.001). Conclusion: Patients with AC presenting beyond 7 days of symptoms have higher conversion rates and longer length of stay associated with SALC. However, patients with less than a week of symptoms should be offered SALC.